Osteonecrosis of the Jaws Associated with Medications with Possible Related Sepsis - Caminha, Raquel D’Aquino Garcia; Viola, Vivian Palata; Costa, Flávia Cristina; Amaral, Ana Livia do; Maluf, Gustavo Valerio; Silva Santos, Paulo Sérgio da (ARCHIVES OF HEALTH INVESTIGATION, 2025)
Sepsis is considered a syndrome that occurs as a result of the release of several cytokines and other mediators in response to an infectious process. It develops in a potentially severe way and has a high mortality rate. The diagnosis of medication-related osteonecrosis of the jaw (MRONJ) is becoming more prevalent, and it is a comorbidity that presents a high risk of infection development. Case reports that relate the diagnosis of sepsis to MRONJ are scarce in the literature, and the need for updates for early diagnosis and effective treatments are crucial in these conditions.